SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN SISWA BARU MENGGUNAKAN METODE MOORA (MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS) - Andi Arisman; Fricles A Sianturi (Sisfokomtek, 2020)
Abstract In determining the new students who are exact and in accordance with the wishes, it is not easy. One of the problems faced by the New Student Admissions Committee (PPDB) each year are the criteria or conditions for admission of new students. Realizing how important it is in determining the right new students, there is no potential for KKN (Corruption, Collusion and Nepotism), it is necessary to establish an Acceptance Decision Support System New Students Using the MOORA (Multi-Objective Optimization on the basis of Ratio Analysis). The system created is expected to make it easier for them the school SD Negeri 097358 Negeri Lawan, Kec. Batu Nanggar, Kab. North Sumatra Simalungun in determining new students who are accepted according to the number of quaternary needed. This new student admission decision support system is a computerized application program, thus it can help the committee to determine candidates of new students who will be accepted. The final result obtained is the result of the determination calculation acceptance of new students by having the ability according to existing criteria predetermined. Based on the analysis results when testing the support system, it can be concluded that this application is very easy to use (perceived ease of use) and is very useful for the State Elementary School 097358 Negeri Lawan, Kec. Dolok Batu Nanggar, Kab. Simalungun-North Sumatra. Keywords : MOORA, New Student Admission, Decision Support System